Pemanfaatan Minyak Jelantah sebagai Bahan Utama dalam Pembuatan Lilin Aromaterapi: Inovasi Kreatif dalam Mendukung Prinsip Ekonomi Sirkular dan Berkelanjutan - Benedicta Bella Puspita Sari; Anggit Dyah Kusumastuti (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
Although often overlooked as household waste, used cooking oil has great potential to produce environmentally friendly products. Fourth semester students of the Business Administration Program were trained to make aromatherapy candles from used cooking oil through this community service activity. The goal was to increase knowledge about the circular economy, encourage creativity, and foster students' entrepreneurial spirit. Socialization, hands-on practice, pre-post test evaluation, and participatory discussion were the methods of the activity. The results showed a significant increase in understanding and recycling skills. This activity shows that innovation based on household waste can support environmental sustainability while producing products with sales value.